Utilization of PEFB reinforced box waste coated super-hydrophobic coating for shoe sole applications - Mohd Fodzi, Muhammad Haikal; Marsi, Noraini; Chow, Li Kien (WARSE, 2020)
This paper presents the utilization of palm empty fruit bunches (PEFB) reinforced with box waste for shoe sole applications. The main objective of this study is to determine the optimum composition of PEFB reinforced with box waste for shoe sole application. The use of PEFB and box waste for shoe sole as alternative to solve the environmental problem and change waste into zero waste which can support the green campaign and attain sustainable environment since both materials are low cost, daily waste materials and environmental friendly to reuse and modify into new products. The preparation of samples was involved grinding process of PEFB fiber and box waste, blending process of different percentage of PEFB in 20%, 40%, 60% and 80% with 50% of box waste, followed by mixing process with epoxy and hardener and finally coated with superhydrophobic coating based palm oil eco-resin by using spray gun techniques. The bonding between fiber-matrix of PEFB and box waste by ratio of 2:1 for epoxy resin and hardener as a binder. The physical test shows that the higher percentages of PEFB which is 80% was produced the lowest density of 1.06g/cm3 and highest porosity up to 0.44%. In term of water droplet test, all the percentages of PEFB produce the water contact angle up to 155.23° with coated superhydrophobic while 75.08° for uncoated surface. It is also conclude that 80% of PEFB reinforced with 50% box waste produced the most optimum composition for shoe sole application in term of physical properties.